Go-Access to Justice System: Optimizing Prodeo Legal Aid as a Strategic Effort to Create Legal Aid Institutions with Integrity and Dignity - Utama, Ananda Luhung Cahya (The Indonesian Journal of International Clinical Legal Education, 2021)
Indonesia is a legal state so that it has logical consequences to provide recognition, guarantee, protection, and legal certainty for every citizen. In accordance with the mandate of Article 28D Paragraph (1) of the Constitution of the Republic of Indonesia, the state is obliged to provide legal protection facilities and legal assistance to citizens who cannot afford it. So that in Article 22 of Law No. 18 of 2003 concerning Advocates, it is mandated to Legal Aid Institutions to provide free legal aid to underprivileged communities which are part of social contribution and social liability. Advocates as officium nobile have an important meaning in the implementation of free legal aid, but in practice in the field, there are still some problems related to the implementation of free legal aid, both from external and internal factors. These problems are in the form of the uneven distribution of prodeo legal aid institutions in Indonesia and the weak monitoring and evaluation of prodeo advocates as well as the absence of performance appraisals and giving rewards to prodeo advocates who excel so that currently the provision of prodeo legal aid is less perceived by the poor. Therefore, the author provides a comprehensive solution through the GO-Access To Justice System as a strategic effort in realizing legal aid institutions with integrity and dignity.